Re-enacting the Bodily Self on Stage: Embodied Cognition Meets Psychoanalysis - Scorolli, Claudia (Frontiers in Psychology, 2019)
The embodied approach to cognition consists in a range of theoretical proposals sharing the idea that our concepts are constitutively shaped by the physical and social constraints of our body and environment. Still far from a mutually enriching interplay, in recent years embodied and psychoanalytic approaches are converging on similar constructs, as the ones of intersubjectivity, bodily self and affective quality of verbal communication. Some efforts to cope with the sentient subject were already present in classical cognitivism: having expunged desires and conflicts from the cognitive harmony, bodily emotions re-emerged but only as a noisy dynamic friction. In contrast, the new, neural, embodied cognitive science with its focus on bodily effects/affects has enabled a dialogue between neuro-cognitive perspectives and clinic-psychological ones, through shared conceptual frameworks. I will address crucial issues that should be faced on this reconciling path. With reference to two kinds of contemporary addictions - Internet Addiction Disorder and Eating Disorders - I will introduce a possible therapeutic approach that is built upon the core role of the acting-sentient Bodily Self in a dynamic-social and affective environment. In the Psychoanalytic Psychodrama the spontaneous reenactment of a past (socially and physically constrained) experience is actualized by means of the other, the Auxiliary Ego. This allows homeostatic and social-emotional affects, i.e. drives and instincts, to be re-experienced by the agent, the Protagonist, in a safe scenario. The director-psychoanalyst smoothly leads back this simulation to the motivated, and constrained, early proximal embodied interactions with the significant others, and to the related instinctual conflicting aims. The psychoanalytic reframing of the classical psychodrama does not merely exploit its original cathartic function, rather stands out for exploring the interpersonal constitution of the self, through an actual “re-somatization” of the psychoanalytic therapy. Unspoken/unspeakable feelings pop up on stage: the strength of this treatment mainly rests on reestablishing the priority of the embodied Self over the narrative Self. By pointing to the possible conflicts between these two selves, this method can broaden the embodied cognition perspective. The psychodramatic approach will be briefly discussed in light of connectionist models, to finally address linguistic and methodological pivotal issues.